Low–lying states of odd nuclei in the south–west 204Pb region - Sharrad, Fadhil; Okhunov, Abdurahim; Abdullah, Hewa; Abu Kassim, Hasan (Publishing House of the Romanian Academy, 2013)
Binding energy of the ground state, energy levels and the B(E2) values of both positive and negative parities for 203,205Au, 203,205Hg, 203-207Tl and 203-207Pb isotopes have been calculated through shell model calculations using the shell model code OXBASH for Windows by employing the Modified Kuo-Herling interaction (khhe) for neutron and proton hole orbits in 208Pb. The binding energy calculations were in good agreement with experimental data. The predicted low-lying levels (energies, spins and parities) and B(E2) values results were reasonably consistent with the available experimental data.